Eurythmy therapy increases specific oscillations of heart rate variability - Edelhäuser, Friedrich (BMC Complement Altern Med, 2015)
BACKGROUND: Mind-body therapies are beneficial for several diseases (e.g. chronic pain, arterial hypertension, mood disorders). Eurythmy therapy (EYT) is a mind-body therapy from Anthroposophic Medicine. In each EYT exercise a short sequence of body movements and simultaneous guided imagery is repeated several times. In this study, the simultaneous effects of two different EYT exercises on cardiac autonomic regulation as assessed by spectral analysis of heart rate variability (HRV) were investigated. METHODS: Twenty healthy subjects (age: 29.1 ± 9.3 years, 13 female) performed two different EYT exercises (EYT-A and EYT-B) for 8 min. Each EYT exercise was compared against two matched control exercises: control exercise 1 (CE1-A and CE1-B) consisted of a repetition of the body movements of the EYT exercise but without guided imagery, control exercise 2 consisted of walking on the spot (CE2-A and CE2-B). Spectral power of HRV during each exercise was quantified on the basis of Holter ECG recordings. RESULTS: During EYT-A the frequency of the peak oscillation in the very low frequency (VLF) band matched the repetition rate of the sequence of body movements (0.02 Hz). Low frequency (LF) oscillations were augmented when compared to the control exercises (EYT-A: 7.31 ± 0.84, CE1-A: 6.98 ± 0.90, CE2-A: 6.52 ± 0.87 ln ms(2), p < 0.05). They showed a peak frequency at 0.08 Hz indicating that the body postures had an impact in HRV. Performing EYT-B increased VLF oscillations when compared to the control exercises (EYT-B: 9.32 ± 0.82, CE1-B: 6.31 ± 0.75, CE2-B: 6.04 ± 0.80 ln ms(2), p < 0.05). The frequency of the peak oscillation again matched the repetition rate of the sequence of body movements (0.028 Hz). CONCLUSIONS: The repetition of the sequence of body movements of both EYT exercises clearly affected cardiac autonomic regulation in a rhythmic manner according to the stimulus of the specific body movements of each EYT exercise. These results offer a physiological basis to develop a rationale for specific clinical indications of these EYT exercises such as stress reduction or prevention of hypertension. TRIAL REGISTRATION: Clinical trials registration number: DRKS00006760 (registered on 10/10/2014, i.e. retrospective registration); view details at http://www.drks.de/DRKS00006760